Which design is better? A lifecycle approach to the sustainable management of artificial habitat‐structures - Dan Parker; Stanislav Roudavski; Chiara Bettega; Luigi Marchesi; Paolo Pedrini; Mattia Brambilla; Kylie Soanes (Conservation Science and Practice)
Abstract This article develops a lifecycle‐based design approach to sustainably provide artificial tree hollows for habitat restoration. It addresses the growing reliance on nest boxes to mitigate impacts from development, forestry, agriculture, and extreme weather events. Although conservation efforts frequently use artificial hollows, their effectiveness and durability remain uncertain. This uncertainty underscores the need for designs that consider environmental, logistical, and economic factors over long periods. Our approach integrates knowledge of how natural hollows form and persist with analyses of how artificial structures function over time to create innovative designs and evaluate their sustainability. We applied this approach to a case study in a storm‐damaged forest in northern Italy, focusing on boreal owls (Aegolius funereus) as the target species. Our modeling assessed the impact of supplying artificial hollows for 50 years at 741 nesting sites, comparing prototypes made from laser‐cut plywood, 3D‐printed plastic, and mycelium blocks. The analysis showed that mycelium offered the most environmentally sustainable option according to our criteria, while plastic remained the most cost‐effective over time. Replacing plastic with mycelium could reduce carbon emissions by 75%, energy consumption by 78%, and waste generation by 81%, but would increase monetary costs by 15.5%. Plywood incurred costs similar to plastic and mycelium but would require substantial design and manufacturing improvements to compete effectively in other criteria. These findings clarify the environmental trade‐offs of different design choices and could guide the development of sustainable conservation strategies in other ecosystems.